Interactive mobile learning using mind mapping approach / Mohd Hafiz Che Ab Aziz - Che Ab Aziz, Mohd Hafiz (2010)
The purpose of this project research is to develop the prototype of mobile learning software for student using Flash. Nowadays, students have at least one mobile device that is mobile phones. Students need an alternate ways so that they can study anytime anywhere using their mobile phones. The project research achieves the objective in developing the prototype of mobile financial application. The conclusion of this research, students really needs an application that can help them in managing their studies and this prototype development would accomplish that needs.